Perancangan Buku Komik City Guide Pariwisata Kota Surabaya Berbasis Ilustrasi Digital Guna Menganalkan Wisata Surabaya - Anugerah, Otto Archio Putra; Budiardjo, Hardman; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2016)
The    purpose of    the    design a    comic    book City Surabaya tourism guide is to introduce and promote                     tourism. Further                     research is                     done using qualitative research methodsthat   do interviews, observation, and   literature to   obtain data that is       used in the       creation of       design       concepts to       support the       comic book city Surabaya tourism guide. The data were analyzed by using multiple stage, apply the reduction         of data, data presentation, and         conclusion. After analyzing         the data, the found discuss      the design      concepts or      keywords "Modern". The      complaint is the latest, cutting  edge,  attitude  andway  of  thinking  and acting  in  accordance with  the demands of the times. The concept  of "Modern" aims to  show  that Surabaya is  a city that has developed technology.Acting, the concept of the menu-the menu is served to infuse the public perceptionthat the public Surabaya willing to learn and thrive in the new stuff. The result of designing a comic book City of Surabaya tourism guide is to introduce and promote tourism city of Surabaya Surabaya and so that people outside the city could've known tourism in Surabaya. Keywords: Design,      city guides, comic       books, tourism, digital illustration,       Surabaya